Marco? Polo! - Scieszka, Jon.; McCauley, Adam (New York : Viking, 2006)
Joe, Sam, and Fred travel to thirteenth-century China, where they disguise themselves as astrologers and meet Marco Polo.
Pages 29-30 deliberately left blank.
School Library Journal.
Book Links (A.L.A.).
Booklist.
3.3
3-6
Keywords: Polo, Marco, -- 1254-1323? -- Fiction; Kublai Khan, -- 1216-1294 -- Fiction; Polo, Marco, -- 1254-1323? -- Fiction; Kublai Khan, -- 1216-1294 -- Fiction; Time travel -- Fiction; Magic -- Fiction; Humorous stories; Time travel -- Fiction; Magic -- Fiction; Humorous fiction; Time travel -- Fiction; Magic -- Fiction; Humorous stories; China -- History -- Fiction